Chloroquine use improves dengue-related symptoms - Borges, Marcos Carvalho (Instituto Oswaldo Cruz, Ministério da Saúde, 2013)
Dengue is the most important arboviral disease in the world. As chloroquine, an antimalarial agent, has shown some antiviral effects, this study evaluated its effect in patients with dengue. A randomised, double-blind study was performed by administering chloroquine or placebo for three days to 129 patients with dengue-related symptoms. Of these patients, 37 were confirmed as having dengue and completed the study; in total, 19 dengue patients received chloroquine and 18 received placebo. There was no significant difference in the duration of the disease or the degree and days of fever. However, 12 patients (63%) with confirmed dengue reported a substantial decrease in pain intensity and a great improvement in their ability to perform daily activities (p = 0.0004) while on the medication and the symptoms returned immediately after these patients stopped taking the medication. The same effect was not observed in patients with diseases other than dengue. Therefore, this study shows that patients with dengue treated with chloroquine had an improvement in their quality of life and were able to resume their daily activities. However, as chloroquine did not alter the duration of the disease or the intensity and days of fever, further studies are necessary to confirm the clinical effects and to assess the side effects of chloroquine in dengue patients.